Two new species of Kallichroma (Bionectriaceae, Hypocreales) from Saudi Arabian mangroves - Abdel-Wahab, Mohamed A.; Bahkali, Ali H.; Jones, E. B. Gareth; Elgorban, Abdallah M.; Abdel-Aziz, Faten A.; Hodhod, Mohamed S.; Al-Hebshi, Mohamed O. (Phytotaxa, 2016)
During an ongoing study of marine fungi in Saudi Arabia, two undescribed Kallichroma species were recorded from decayed intertidal wood of Avicennia marina from two mangrove stands along the Red Sea coast and the Arabian Gulf coast in Saudi Arabia. Kallichroma asperum sp. nov. is characterized by rough ascospores cell walls surrounded by a granular sheath. Kallichroma ellipsoideum sp. nov. is characterized by its small sized hyaline ascomata, asci and ascospores. Both new species have 3 or 8-spored asci and perithecoid or confluent ascomata with large, globose papillae. Phylogenetic analyses of the combined SSU and LSU rDNA sequences placed the two new species in the family Bionectriaceae.